Commentary about mesenchymal stem cells and scarred vocal folds - Alexia Mattei; Jérémy Magalon; Mélanie Velier; Françoise Dignat-George; Antoine Giovanni; Florence Sabatier (Stem Cell Research & Therapy, 2020)
Abstract A commentary to “Hertegård, S., Nagubothu, S.R., Malmström, E. et al. Treatment of vocal fold scarring with autologous bone marrow-derived human mesenchymal stromal cells - first phase I/II human clinical study. Stem Cell Res Ther 11, 128 (2020)” concerning the surgical intervention including a scar resection, the use of the Voice Handicap Index, the surgical and regulatory points of view regarding the inclusion of patients with laryngeal carcinomas history, and the side effects of bone marrow harvesting.